Cutting-edge genetic techniques for optimizing eggplant (Solanum melongena) cultivar performance - Guru Prasad, Manickam; Arul, L; Sathiyamurthy, V A; Vijayalakshmi, D; Kumar, K K (Plant Science Today, 2025)
Brinjal (Solanum melongena L.), a crucial solanaceous vegetable crop, faces significant challenges from biotic stressors like pests and diseases, as well as abiotic stressors such as drought and salinity. Conventional breeding methods are limited in effectively addressing these complex traits. Nevertheless, advancements in molecular breeding, genetic engineering and tissue culture techniques have revolutionized brinjal improvement. Marker-assisted selection (MAS) has enabled the identification and incorporation of quantitative trait loci (QTLs) associated with resistance to bacterial wilt, shoot and fruit borer and enhanced yield attributes. Genetic engineering approaches, such as the development of Bt brinjal, have provided effective pest resistance while minimizing pesticide dependency. Tissue culture methods, including anther culture, have facilitated the rapid development of double haploid (DH) lines with improved fruit quality and tolerance to low temperatures. These biotechnological tools present promising solutions to mitigate stress factors while improving yield, quality and sustainability in brinjal cultivation. Future research should focus on integrating CRISPR/Cas9 gene editing with MAS to accelerate trait-specific improvements and utilize wild relatives for novel gene introgression.